2006
DOI: 10.1002/adma.200600647
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Biochemical and Biomechanical Patterning of Hydrogels for Guiding Cell Behavior

Abstract: The ability to tailor the biochemical and biomechanical properties of 3D materials at the microscale is important for a range of biotechnology applications, including the engineering of complex tissues, the development of biosensors, the elucidation of cell-cell and cell-material interactions, and the guidance of cellular differentiation. [1,2] To this end, techniques have emerged for the fabrication of 3D microcontrolled materials, including conventional photolithographic patterning, [3,4] electrochemical dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
333
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(337 citation statements)
references
References 31 publications
(33 reference statements)
1
333
0
1
Order By: Relevance
“…While early efforts generated patterns by UV exposure through a simple mask, 21 recent work has become far more elaborate. For instance, Hahn et al 16 showed that two-photon activation can generate three-dimensional patterns of acrylated PEG with microscale resolution throughout the bulk of the gel.…”
Section: Photopatterningmentioning
confidence: 99%
“…While early efforts generated patterns by UV exposure through a simple mask, 21 recent work has become far more elaborate. For instance, Hahn et al 16 showed that two-photon activation can generate three-dimensional patterns of acrylated PEG with microscale resolution throughout the bulk of the gel.…”
Section: Photopatterningmentioning
confidence: 99%
“…PEG has a well-established chemistry and long history of safety in vivo. Addition of acrylate groups flanking the PEG chain allows for photo or chemical cross-linking of a PEGDA macromer solution, as well as incorporation of biomolecules such as protease-degradable sites, adhesive ligands, and growth factors (14)(15)(16). A major strength of this strategy is the modular "plugand-play" design of the base hydrogel system, which allows the tailoring of the biochemical and mechanical properties of the delivery vehicle.…”
mentioning
confidence: 99%
“…Furthermore, hydrogels can also be structured photolithographically, taking advantage of diffusion processes. Three-dimensional structuring at the microscale results in the ability to spatially tailor biomechanical and biochemical material properties [52].…”
Section: Biomedicinementioning
confidence: 99%